2020
DOI: 10.1001/jamanetworkopen.2019.19681
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Prenatal and Childhood Antibiotic Exposure With Obesity at Age 4 Years

Abstract: IMPORTANCE Although antibiotics are associated with obesity in animal models, the evidence in humans is conflicting. OBJECTIVE To assess whether antibiotic exposure during pregnancy and/or early childhood is associated with the development of childhood obesity, focusing particularly on siblings and twins. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional national study included 284 211 participants (132 852 mothers and 151 359 children) in New Zealand. Data analyses were performed for 150 699 children for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 30 publications
1
41
3
3
Order By: Relevance
“…In this study, it was clear that antibiotic treatment dramatically altered the intestinal microbiota composition immediately, but the effects induced by a shortterm therapeutic dose of ceftriaxone on intestinal microbiota at least at the phylum level did not appear to continue to adulthood. Recently, research has explored the relationship between obesity and antibiotic treatment, especially in infancy or childhood, but the results lacked consistency [46][47][48]. In our study, antibiotic use induced the dysbiosis of the intestinal microbiota during early life, although this effect did not continue to adulthood.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, it was clear that antibiotic treatment dramatically altered the intestinal microbiota composition immediately, but the effects induced by a shortterm therapeutic dose of ceftriaxone on intestinal microbiota at least at the phylum level did not appear to continue to adulthood. Recently, research has explored the relationship between obesity and antibiotic treatment, especially in infancy or childhood, but the results lacked consistency [46][47][48]. In our study, antibiotic use induced the dysbiosis of the intestinal microbiota during early life, although this effect did not continue to adulthood.…”
Section: Discussionmentioning
confidence: 57%
“…Our findings must be interpreted in the light of a recent cross-sectional study 42 of 284,211 participants that included siblings and twins in New Zealand and that analyzed prenatal and early infancy antibiotic exposure (first two years) and its association with obesity at 4 years. The study found that both prenatal and early infancy exposure to antibiotics were independently associated with obesity at 4 years in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 92%
“…Observational studies in high resource settings have shown an association between antibiotic consumption and increased child growth, leading to concerns about antibiotic consumption and childhood obesity [ 22 , 23 ]. Potential biases including unmeasured confounding limit the ability to draw causal conclusions from these studies [ 24 ]. Randomized controlled trial evidence has generally shown increased growth among children with known acute or chronic illness following antibiotic administration in lower resource settings [ 10 ].…”
Section: Discussionmentioning
confidence: 99%